Efeito de tityustoxina gama marcada com tecnecio 99m sobre o sistema colinérgico central em ratos - Silmara Araujo Amaral da Silva (2008)
The scorpion toxin, TiTX- , affects central nervous system even when injected by subcutaneous via, as it happens in scorpion stings. However, there is no direct evidence of its presence in brain in this circumstance. The goal in this work was to demonstrate that TiTX- can cross the blood-brain barrier in young well-nourished and malnourished animals, reaching the brain and inducing the acetylcholine release. Fourgroups of rats were used: NC (normal control); NE (normal stimulated by toxin injection); DC (malnourished control); DE (malnourished stimulated by toxin injection). The malnourished groups received 60% of the diet consumed by the well-nourished groups. At 21 days of life, the groups NE and DE received intraperitoneal injection of [99mTc]-TiTX-ã and the groups NC and DC received intraperitoneal injection of themedium used for technetium labeling. After ninety minutes animals were decapitated and the radioactivity in their brain was counted in gamma scintillation equipment. The brains were homogenized and aliquots used to assay acetylcholine by chemiluminescent procedure. The food restriction decreased body and brain weight of the malnourished animals 24.63 } 1.13 g; 0.94 } 0.06, respectively, in relation to well nourished animals 41.62 } 7.01 g; 1.09 } 0.04 g. The well-nourished animals took 50% more radioactive toxin, evaluated by cpm in the organ related to that injected, than that in the malnourished animals (0,33 } 0,04% versus 0,17 } 0,06%). TiTX- crossed brains blood barrier in all animals that received toxin injection promoting increase in theacetylcholine concentration in brain of the animals and in greater quantity in well nourished rats (nmol ACh/g de tecido } EPM): NC 1,80 } 0,44; NE 3,15 } 0,75; DC 1,22 } 0,47 e DE 2,17 } 0,21. It is concluded that TiTX- cross the blood-brain barrier and fulfills its function, as already proved, activating sodium channels and augmenting acetylcholine concentration in the central nervous system.